Atributos taxonômicos e funcionais de Polychaeta como ferramentas ecológicas para o monitoramento de estuários tropicais - Gomes, Wilma Izabelly Ananias (2020)
The balance between fresh water input and evaporation can be used to classify estuaries as positive and inverse. Positive estuaries have a progressive saline gradient downstream of the sea, while in inverse estuaries the highest salinity values are found upstream of the sea. Although they differ in terms of the saline gradient, both estuaries are productive, biodiverse and dynamic ecosystems, although human actions have been putting this status at risk. In this context, it is essential that biomonitoring programs adopt methods that provide accurate, fast and low-cost results to assess the environmental quality of estuaries. In addition, understanding the relationship between taxonomic wealth and functional diversity is fundamental, in view of the changes that human impacts have on biodiversity. Thus, chapter 1 aimed to test the efficiency of sieves with 1 mm mesh and the combination of 1 + 0.5 mm meshes in estimating the composition and structure of the Polychaeta fauna along the estuarine gradient during the rainy and dry periods. The main results indicate that the inclusion of the 0.5 mm mesh data did not increase the statistical power in detecting significant differences in the structure of the Polychaeta fauna when using the 1 mm mesh or combined meshes. However, exclusive taxa of the 0.5 mm mesh can contribute with essential information, especially when the assessment is made purely based on taxonomic wealth. Therefore, we suggest that the 1 mm mesh can be used in biomonitoring studies in tropical estuaries, as long as the assessment is made based on the combination of structural attributes and diversity indexes. Chapter 2 aimed to evaluate the relationship between taxonomic richness (S) with functional richness (FRic), functional uniformity (FEve), functional divergence (FDiv) and functional redundancy (FRed) of Polychaeta in typical tropical estuaries and tropical semiarid estuaries, northeast of Brazil. The main results show that in the semi-arid tropical estuaries, FRic increased with taxonomic richness, as new combinations of functional categories were added to the community, also causing the reduction of FRed. FEve and FDiv decreased with taxonomic wealth, suggesting an increase in the functional overlap of the community. While in typical tropical estuaries, only FRic showed a significant positive relationship, the other functional components were not related to taxonomic richness. Therefore, the components of functional diversity respond in different ways to taxonomic wealth, depending on the intensity of anthropogenic disturbances in each ecosystem. The data generated at the end of the thesis contribute with unprecedented information of great relevance to the scientific community and the managers of environmental agencies in Brazil and worldwide.